2014
DOI: 10.1007/s13201-014-0170-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of principal component analysis in grouping geomorphic parameters of a watershed for hydrological modeling

Abstract: Principal component analysis has been applied to 13 dimensionless geomorphic parameters on 8 subwatersheds of Kanhiya Nala watershed tributary of Tons River located in Part of Panna and Satna district of Madhya Pradesh, India, to group the parameters under different components based on significant correlations. Results of principal component analysis of 13 geomorphic parameters clearly reveal that some of these parameters are strongly correlated with the components but texture ratio and hypsometric integral do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…However, when the independent parameters were normalized, more than two parameters were required (Table S4 in supporting information). The PCA results supported, to some extent, previous findings that stressed the importance of not only the watershed slope but also the drainage density and the shape of the watershed shape for the interaction between surface water and groundwater (Sharma et al, ). However, this study also identified subsurface hydraulic conductivity (soil type) as important both as an independent parameter and as an explanation for the degree of interaction between deep groundwater and the hyporheic zone.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, when the independent parameters were normalized, more than two parameters were required (Table S4 in supporting information). The PCA results supported, to some extent, previous findings that stressed the importance of not only the watershed slope but also the drainage density and the shape of the watershed shape for the interaction between surface water and groundwater (Sharma et al, ). However, this study also identified subsurface hydraulic conductivity (soil type) as important both as an independent parameter and as an explanation for the degree of interaction between deep groundwater and the hyporheic zone.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the PCA was applied on nonnormalized and normalized (with Ciμiσi, and with Ciμi) forms of the selected independent parameters, where C i is an independent parameter and μ i and σ i are the mean value and standard deviation of each independent parameter i for all the selected reaches, respectively. Previous studies suggested that two to three watershed parameters stand for the dominant loadings to the principal components (Onesti & Miller, ; Sharma et al, ). The investigation here adds subsurface parameters, such as hydraulic conductivity and Quaternary deposit thickness, which are believed to be important for surface water‐groundwater interaction.…”
Section: Methodsmentioning
confidence: 99%
“…The authors used a quantitative analysis of morphometric variables based on RS and GIS techniques. PCA was applied based on linear, areal, and shape variables of 8 SW at the Kanhiya Nala watershed, a tributary of Tons River, Madhya Pradesh, India [26], to categorize the used parameters under various components using correlation analysis. The results revealed that some parameters have strong correlation with the components; however, hypsometric integral and texture ratio did not indicate any correlation with the components.…”
Section: Introductionmentioning
confidence: 99%
“…To pacify the effect of nonuniform rainfall distribution and to aid rain water harvesting in semi-arid regions grouping of geomorphic parameters of a watershed is important for hydrologic modeling using principal component analysis (PCA) (Sharma et al 2015;Farhan et al 2017;Liu et al 2017). PCA can also be used for evaluation and management of water quality (Parinet et al 2004;Gajbhiye et al 2015aGajbhiye et al , 2015b and also in the development of water sustainability index (Ali 2009).…”
Section: Introductionmentioning
confidence: 99%